Pd-1 / pd-l1 inhibitors for the treatment of cancer (2024)
The invention relates to methods of treating cancer in a subject, comprising administering to the subject a therapeutically effective amount of an inhibitor of the interaction between the PD-1 receptor and its ligand PD-L1.